Diseases of the Liver in Children Evaluation and Management - Murray, Karen F.; Horslen, Simon; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2014)
Diseases of the Liver in Children: Evaluation and Management provides a comprehensive, state-of-the art review of pediatric liver disease, with a practical approach useful for the primary care provider or general gastroenterologist.  With an emphasis on tables and images, this book serves as a reference for understanding basic hepatic processes and the significance of laboratory findings. It also discusses the state of the art of diagnosis and treatment of diseases that affect the pediatric liver.  The text captures the key elements of treatment and monitoring important for the primary care provider partnering in the care of these patients with pediatric hepatologists. The current state of transplantation and other surgical approaches are also discussed.  The importance of aggressive bowel rehabilitation in the prevention of end-stage total parenteral nutrition-induced liver disease is also covered.        Written by experts in their fields and including the most up to date clinical information,  Diseases of the Liver in Children: Evaluation and Management serves as a very useful resource for physicians.
Anatomy and Development of the Liver -- Normal functional biology of the liver -- Laboratory assessment of hepatic injury and function -- Mechanisms of Liver Injury -- Radiology of the liver in children -- Phenotypes of liver disease in infants, children and adolescents children -- Psychosocial, cognitive, and quality of life considerations in the child with liver disease and their family children -- Metabolic liver disease - Part 1 -- Metabolic liver disease - Part 2 -- Neonatal Hemochromatosis and Gestational Alloimmune Liver Disease -- Alagille Syndrome -- Idiopathic Neonatal Hepatitis and it’s Differential Diagnoses -- Biliary atresia -- Choledochal Cysts and fibrocystic diseases of the liver -- Infections of the Liver -- Autoimmune Hepatitis and Sclerosing Cholangitis -- Parental Nutrition Associated Liver Disease in Pediatric Patients: Strategies for Treatment and Prevention -- Non-alcoholic Fatty Liver Disease and Non-alcoholic Steatohepatitis -- Drug induced liver injury in children: A structured approach to diagnosis and management -- Gallstone disease in children -- Vascular Liver Disease -- Hepatic Tumors -- Acute Liver Failure -- Intensive Care Management of Children With Liver Failure -- Chronic Liver Diseases, Cirrhosis and Complications: Part 1: Portal Hypertension, Ascites, Spontaneous Bacterial Peritonitis (SBP) and Hepatorenal Syndrome (HRS) -- Chronic Liver Disease, Cirrhosis and Complications: Part 2 – Hepatic encephalopathy and other systemic effects -- Nutrition in Children with Liver Disease: Evaluation and Management -- Liver Transplantation -- Liver in systemic disease.
Keywords: Gastroenterology .; Hepatology; Pediatrics; Gastroenterology; Hepatology; Pediatrics